2005
DOI: 10.1242/jcs.01729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Walker A mutation (K86M) on oligomerization and surface targeting of the multidrug resistance transporter ABCG2

Abstract: The ATP binding cassette (ABC) half-transporter ABCG2 (MXR/BCRP/ABCP) is associated with mitoxantrone resistance accompanied by cross-resistance to a broad spectrum of cytotoxic drugs. Here we investigate the functional consequences of mutating a highly conserved lysine in the Walker A motif of the nucleotide binding domain (NBD) known to be critical for ATP binding and/or hydrolysis in ABC transporters. The mutant (ABCG2-K86M) was inactive as expected but was expressed at similar levels as the wild-type (wt) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 35 publications
(55 reference statements)
6
50
1
Order By: Relevance
“…We found that Ala substitution of Pro 485 in TM3 significantly reduced efflux of BODIPY-prazosin by 70%, but had no effect on efflux of mitoxantrone and Hoechst 33342 (94 (96,98). However, another study showed that the activity loss caused by mutations of Lys 86 was possibly due to altered subcellular localization and cell surface targeting of BCRP (97). More information about mutations and their effects on function and expression of BCRP can be found in an open access database (http://abcmutations.hegelab.org/).…”
Section: Mutagenesis Analysismentioning
confidence: 79%
“…We found that Ala substitution of Pro 485 in TM3 significantly reduced efflux of BODIPY-prazosin by 70%, but had no effect on efflux of mitoxantrone and Hoechst 33342 (94 (96,98). However, another study showed that the activity loss caused by mutations of Lys 86 was possibly due to altered subcellular localization and cell surface targeting of BCRP (97). More information about mutations and their effects on function and expression of BCRP can be found in an open access database (http://abcmutations.hegelab.org/).…”
Section: Mutagenesis Analysismentioning
confidence: 79%
“…However, the impact is much less than observed with K86M, a mutation in Walker A that has been reported to retain dimerization with a functional dominant negative effect. (35) Evaluating the effect of a charged residue at the 553 site, we replaced the glycine with glutamic acid (G553E) and transfected HEK 293 cells. In case of the Drosophila white protein, the corresponding, X-ray induced G589E mutation was described as presumably interfering with heterodimerization (22).…”
Section: Resultsmentioning
confidence: 99%
“…homodimers through disulfide bond mediated by cysteine 603; however, such covalent intermolecular link does not appear to be prerequisite for BCRP to exert its transport activity (25,26). It remains to be investigated how phosphorylation of Thr-362 affects the intermolecular interaction between BCRP dimers or multimers.…”
Section: Discussionmentioning
confidence: 99%